Potential of Nomuraea rileyi (Farlow) Samson as a Entomopathogen to Helicoverpa armigera Hubner on Cotton - IGAA. INDRAYANI (Puslitbang Perkebunan, 2011)
Naturally, occuring entomopathogens are important as a regulatory factors in insect pest population. N. rileyi isolated from H. armigera cadavers on corn silks and leaves of tomato and cotton is an important entomopathogenic fungi causing natural mortality in more than 10 lepidopteran insects throughout the world. One of these pests is cotton bollworm or corn budworm, H. armigera was found naturally infected by N. rileyi around Malang and Lamongan, East Java. Field observation recorded that number of infected larvae by N. rileyi increased every year in the field. This indicated that epizootic of N. rileyi developed rapidly in host population. To study the potency of N. rileyi as a mortality factor of H. armigera, a series of test should be arranged e.g. isolation, purification, biological characteristic test, such as growth rate, conidia production, and testing of virulence against target insect pest. N. rileyi was isolated from infected larvae of H. armigera in the field, then purified and re-cultured on Sabouraud Maltose Agar with yeast extract (SMAY) medium. The objective of this paper is to inform the potency of N. rileyi as a bio control agent against H. armigera. There were two strains of N. rileyi, MA 01 and LG 02 collected from H. amigera larvae cadaver from Malang and Lamongan, East java. Laboratory test on germination showed that the germination rate of both strains MA 01 and LG 02 were faster on SMAY media (1,25-1,27 mm/day) than that on SMAY+rice extract (SMAYR) media (0,99-1,07 mm/day). Yield of conidia cultured on SMAY was higher on LG 02 than on MA 01 as 3,9 x 109 conidia/ml and 1,7 x 109conidia/ml, respectively. Strain LG 02 was more virulence than MA 01 against second instar of H. armigera with 76 and 64% of percentage mortality, respectively. Concentration of N. rileyi conidia for 50% mortality of tested larvae (LC50) was 5,2 x 106 conidia/ml and 7,2 x 106 conidia/ml for LG 02 and MA 01, respectively with average LT50 were 5,9-8,4 days. However, these early studies need further testing to find out the whole potency of N. rileyi in controling of H. armigera, mainly study on virulence against other insect host, compatibility to other control methods and suitable technique for mass production, such as effective and efficient. Key words: Entomopathogen, Nomuraea rileyi, isolate, strain, mortality, conidia, virulence